EFEKTIVITAS MODEL PEMBELAJARAN COOPERATIVE INTEGRAD READING AND COMPOSITION TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS - Salim, Emil; Yulia, Yulia; Utami, Nita Putri (UIN Imam Bonjol Padang, 2024)
The mathematical problem solving ability of class VIII students at MTsN 1 kota Payakumbuh is still relatively low. The Cooperative Integrated Reading and Composition learning model is one of the proposed solutions. This article aims to describe the mathematical problem solving abilities of students who study with the Cooperative Integrad Reading and Composition learning model as being higher than the mathematical problem solving abilities of students who study with scientific learning in class VIII MTsN 1 Kota Payakumbuh. This research is a type of quasi-experimental research with a randomized control group only design. The population of this study was all class VIII at MTsN 1 Kota Payakumbuh. The research sample was class VIII.7 as the experimental class and class VIII.9 as the control class. The instrument used is a test of mathematical problem solving abilities. The test results in the experimental class mean the mathematical problem solving ability of students taught using the Cooperative Integrad Reading and Composition learning model was 79.01 and in the control class was 69.17. The data analysis technique used is the one-way t-test. Hypothesis test results using the t-test with α=0,05 at the 95% confidence level obtained t_hitung (3,43)t_tabel (1,67) then H_0 is rejected and H_1 is accepted, this means that the mathematical problem solving abilities of students who study using the Cooperative Integrad Reading and Composition learning model are higher than the mathematical problem solving abilities of students who study using scientific learning